STRATEGI MARKETING MIX PADA USAHA KULINER DAPOER RENDANG TELUR RIRYDI KAWASAN DESTINASI WISATA KULINER KOTA PAYAKUMBUH - Irfan Hakim; Amsah Hendri Doni (Jurnal Ekonomi dan Bisnis, 2025)
This research is based on the background of the Dapoer Rendang RIRY Business which is a Culinary Souvenir Business typical of Ranah Minang, namely in the form of various types of Rendang which has been established for a long time but still has not maximised the Marketing Mix Strategy in increasing sales. The implementation of the Dapoer Rendang RIRY Marketing Mix Strategy is the focus of this research, as well as to find out and analyse what obstacles or obstacles are experienced by Dapoer Rendang RIRY in implementing the Marketing Mix Strategy. Field research is a key component of this qualitative research approach. Observation, interviews, and documentation are the methods used to collect data. By using research tools such as SWOT Matrix Analysis, there are four kinds of data analysis strategies used: data collection, data reduction, data presentation, and conclusion drawing. From the results of the study, Dapoer Rendang RIRY will continue to increase sales if it applies the S-O Strategy in the business, by maximising the strengths possessed and maximising the opportunities that exist, the things that can be done by Dapoer Rendang RIRY are first, with the ease of getting raw materials so that the many types of Rendang produced are guaranteed without preservatives. Second, with the location in the Rendang village and also the discount will be a big enough attraction. Third, when clean raw materials are also described in online media promotions, it will be more attractive to customers. Fourth, with good product quality and good service to new and old consumers will increase sales. Fifth, by increasing product packaging innovation and customer service, it will be able to attract many new customers. Furthermore, in overcoming the obstacles and obstacles of Dapoer Rendang RIRY, what can be done is to form a managerial such as forming good marketing management and formulating risk management in order to be able to face all the obstacles and obstacles in the business. in order to be able to face all the obstacles and obstacles in the application of Marketing Mix Strategies that may occur in the future.